Sharia Capital Market in Indonesia - Fitri Ramdani; Sakinah Azzahra; Mukhtar Lutfi; Lince Bulutoding (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
The Islamic capital market has become a strategic component of the Islamic financial system by providing investment instruments that comply with Sharia principles while supporting sustainable economic development. Along with the growing public awareness of halal investment, the Islamic capital market in Indonesia has experienced significant growth. This study aims to analyze the concept of the Islamic capital market in Indonesia, examine its differences from the conventional capital market, identify the factors influencing its development, and evaluate the opportunities and challenges it faces. This research employs a qualitative descriptive approach using the library research method by reviewing scientific literature, laws and regulations, and other relevant references. The findings reveal that the development of the Islamic capital market is driven by supportive government regulations, increasing Islamic financial literacy, advancements in market infrastructure and financial technology, product diversification, and stable economic conditions. However, its development continues to face challenges, including limited public literacy, inadequate product innovation, competition with the conventional capital market, and the need for stronger regulatory support. Therefore, greater collaboration among the government, regulators, financial institutions, academics, and the public is essential to enhance financial literacy, encourage product innovation, strengthen regulatory frameworks, and ensure the competitiveness and sustainability of Indonesia's Islamic capital market.